IMPLEMENTATION OF THE 'START WITH A QUESTION' STRATEGY IN HISTORY LEARNING OUTCOMES FOR CLASS XI STUDENTS ATSMA NEGERI 3 KENDARI - Suharni Suddin (Adisam Publisher, 2025)
This research employs an experimental design with test techniques, aiming to analyze descriptively and inferentially: (1) the influence of the